Functional Characterization of the 1-Deoxy-D-Xylulose 5-Phosphate Synthase Genes in Morus notabilis - Zhang, Shaoyu; Ding, Guangyu; He, Wenmin; Liu, Kai; Luo, Yiwei; Tang, Jiaqi; He, Ningjia (Frontiers in Plant Science, 2020)
Terpenoids are considered to be the largest group of secondary metabolites and natural products. Studies have revealed 1-deoxy-D-xylulose 5-phosphate synthase (DXS) is the first and rate-limiting enzyme in the plastidial methylerythritol phosphate pathway, which produces isopentenyl diphosphate and its isoform dimethylallyl diphosphate as terpenoid biosynthesis precursors. Mulberry (Morus L.) is an economically and ecologically important perennial tree with multiple secondary metabolites, including terpenoids that protect plants against bacteria and insects and may be useful for treating human diseases. However, there has been relatively little research regarding DXS genes in mulberry and other woody plant species. In this study, we cloned and functionally characterized three Morus notabilis DXS genes (MnDXS1, MnDXS2A, and MnDXS2B). Bioinformatics analyses indicated MnDXS1 belongs to clade 1, whereas MnDXS2A and MnDXS2B are in clade 2. The three encoded MnDXS proteins are localized to chloroplasts. Additionally, substantial differences in MnDXS expression patterns were observed in diverse tissues and in response to insect feeding and a methyl jasmonate treatment. Moreover, the overexpression of MnDXS1 in Arabidopsis thaliana increased the gibberellic acid content and resulted in early flowering, whereas the overexpression of MnDXS2A enhanced root development. Our findings indicate that MnDXS functions vary among the clades, which may be useful for further elucidating the DXS roles in mulberry.